Response of Sweet Corn Varieties Paragon and Talenta to Urine of Fermented Goats Rhizomes of Zingiberaceae on Ultisol - Widodo Haryoko; Yopa Dwi Mutia; Ermawati Ermawati; Dwi Rahayu (University of Prof. Dr. Hazairin, SH, 2023)
The experiment aimed to determine the response of sweet corn varieties of paragon and talent to the urine of goats fermented rhizomes on ultisol. The experiment was conducted with ultisol-type soil from April to August 2022 at BPP Koto Balingka, Nagari Parit, Koto Balingka District, West Pasaman Regency. The experiment was conducted with a two-factor Complete Randomized Design (RAL). The first factor is four kinds of fermented goat urine: Goat urine, Fermented goat urine ginger, Fermented goat urine turmeric, and Fermented goat urine galangal, each 100 ml L-1. The second factor of the two varieties of sweet corn is 1) Paragon and 2) Talenta. The combination of the two factors was repeated four times so that there were 32 experimental units. The experimental results showed that (1) Fertilization of POC of fermented goat urine of Zingiberacea rhizomes increased plant height and ILD, (2) Fertilization of POC of fermented goat urine of Zingiberacea rhizomes accelerated flowering, increased the weight of cobs without lids, a diameter of cobs without loots, and weights of 1000 seeds, (3) The ability of the Talenta variety to respond to POC of goat urine fermented galangal was higher than the Paragon variety, namely by showing higher production of 20,02 t ha-1 compared to the production of the Paragon variety with a production of 17,04 t ha-1.